KEARIFAN LOKAL PADA KOMUNITAS ADAT KEJAWEN BONOKELING - Arnis Rachmadhani (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2015)
This is a qualitative research that is conducted in Kejawen (indigenous tradition in Java) communities in Pekuncen village, Jatilawang district, Banyumas regency. Data is collected by using interviews, observation, and documentation. This research describes the spread of traditional Javanese by Kyai Bonokeling which has variety of rituals such as unggahan and udunan that can be an inspiration for building or strengthening faith in religious harmony. Unggahan or sadran activities describe a preparation conducted by farmers in facing rice planting season, while turunan activities represent a symbol of gratitude in having rice harvest season. Unggahan or sadran activities also have meaning to face the fasting month and turunan is as a sign of completion.